2019
DOI: 10.1177/1474515119863178
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing self-management priority setting and decision-making among Chinese patients with acute coronary syndrome and type 2 diabetes mellitus

Abstract: Background: Priority setting and decision-making in relation to self-management of multiple conditions is particularly challenging for both patients and health professionals. The aim of this study was to validate a conceptual model of self-management priority setting and decision-making in multimorbidity and confirm factors that influence self-management prioritizing and decision-making in a sample of patients with acute coronary syndrome and type 2 diabetes mellitus. Methods: This was a qualitative study usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…Seven of these studies 35‐41 aimed to research financial burden or a related concept. The remaining 39 studies 34,42‐79 researched several issues including self‐management, 42,44‐46,48,55,57,60 adherence 43,52,56,62,64 and living with multimorbidity 63,66,67,70,75 . There were 4,364 unique participants in total.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seven of these studies 35‐41 aimed to research financial burden or a related concept. The remaining 39 studies 34,42‐79 researched several issues including self‐management, 42,44‐46,48,55,57,60 adherence 43,52,56,62,64 and living with multimorbidity 63,66,67,70,75 . There were 4,364 unique participants in total.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies, 73,74 used online questionnaires and included 2,689 participants, while the remaining 44 studies included 1,675 participants. From the forty‐one studies 36‐47,49‐68,70‐79 reporting participants’ gender, 1,386 (63.3%) were male, 799 (36.5%) were female, one (0.0004%) was a transgender female and two (0.001%) were described as ‘other’. The mean age for participants was 53.6 years (from 28 studies 36,37,39,40,43‐45,47‐50,52,53,56,59‐61,63,65‐68,71,74‐78 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fitzpatrick et al 17 used photovoice to photograph Asian elders' perceptions of scenes promoting or acting as barriers to cardiovascular health. Liu et al 18 found that different attitudes influenced self-management priority setting and decision-making among Chinese patients with acute coronary syndrome and type 2 diabetes mellitus through deductive directed content analysis. As such, adopting patients' attitudes can lead to a better understanding of how an individual's real demands on treatments to achieve the setting-goals, help to tailor individualized self-management strategies and reduce the financial burdens at all levels.…”
Section: Introductionmentioning
confidence: 99%